Human leukocyte antigen class II and type 1 diabetes in Latin America: A combined meta-analysis of association and family-based studies (2011)
Conclusions from association studies could be spurious because of population stratification; therefore we combined association with family studies seeking to confirm which human leukocyte antigen (HLA) class II alleles/haplotypes were associated with type 1 diabetes (T1D) in the admixed Latin America. By calculating the effect summary odds ratios (OR) and their 95% confidence intervals (95% CI), data up to June 2010 showed that risk associations were observed with DRB1*0301-DQA1*0501-DQB1*0201 (odds ratio [OR]: 7.51; 95% confidence interval [CI]: 3.69-15.25) and DQB1*0302 in presence of DRB1*0405 (OR: 11.64; 95% CI: 3.15-43.01) or DRB1*0401 (OR: 5.85; 95% CI: 3.07-11.14). In contrast, DRB1*0404-DQB1*0302 had a nonsignificant TID risk (OR: 2.23; 95% CI: 0.91-5.43). T1D protective associations were observed with DRB1*11-DQA1*0501-DQB1*0301 (OR: 0.24; 95% CI: 0.1-0.56) and DRB1*15-DQA1*0102-DQB1*0602 (OR: 0.35; 95% CI: 0.17-0.73). These results were similar to those observed in Caucasian and other populations, thus highlighting the primary role of class II HLA in T1D regardless of ethnicity. A DRB1*04 risk hierarchy was confirmed with the DRB1*0405 being in the top. A binding prediction analysis disclosed possible receptor-ligand interactions in the HLA-antigenic peptide complex. © 2011 American Society for Histocompatibility and Immunogenetics.